Prognostic impact of severe anemia (hemoglobin <10g/dL) during treatment with dual antiplatelet therapy after hospital discharge for acute coronary syndrome. (25th November 2020) - Campos, I; Oliveira, C; Pires, C; Medeiros, P; Flores, R; Mane, F; Braga, C; Gaspar, A
Abstract: Introduction: In recent years, the use of invasive strategies has become the generalized approach in the management of patients with acute coronary syndrome (ACS), justified by the associated prognostic benefit due to reduced mortality and the evolution of percutaneous coronary intervention (PCI). However, the benefits of an invasive approach in ACS are unclear in the population with significant anemia, as anemia is strongly associated with increased risk of morbidity and mortality in these patients. Aim: To determine the ischaemic vs. bleeding risks from patients with severe anemia (hemoglobin <10 g/dL) during treatment with Dual Antiplatelet Therapy (DAPT) after an ACS undergoing PCI. Methods: From a national multicentre registry, we analyzed 17 370 ACS pts. Pts were divided into two groups: group 1 - pts with severe anemia (hemoglobin <10g/dL) (n=557, 3.2%); group 2 - pts without severe anemia (hemoglobin 10g/dL) (n=16813, 96.8%). Primary endpoint was the occurrence of a composite of death and adverse cardiovascular events (stroke, reinfarction, and rehospitalization of cardiovascular etiology) at 1 year. Results: The sample consisted in 73.4% men and 26.6% women, with mean age of 66±14 years. The incidence of severe anemia was 3.2%. Group 1 pts were older (75±12 vs 66±14, p<0.001), had a higher proportion of women (47.6% vs 25.9%, p<0.001), diabetes (55% vs 30.6%, p<0.001), hypertension (81.8% vs 68.2%, p<0.001) and chronic kidney disease (29.2% vs 5.2%, p<0.001). During hospitalization, group 1 had more heart failure (35.3% vs 15.1%, p<0.001), worst LVEF (27.3% vs 17.3%, p<0, 001), bleeding (7.6%% vs 1.3%, p<0.001) and transfusion (23.4% vs 1%, p<0.001). During hospitalization, group 2 pts were more likely to undergo revascularization (82.9% vs 89.4%, p<0.001) and double antiaggregation (82.5% vs 95%, p<0.001). A multivariate analysis identified age [OR 1.48, 95% CI 1.32 to 1.89; p<0.001] and feminine sex [OR 2.21, 95% CI 1.89 to 3.61; p<0.001] as independent predictors of severe anemia during hospitalization. Patients with severe anemia had longer hospital stay (9 days vs 6 days; p<0.001), and higher 6-month mortality (8.7% vs. 2.9%; p<0.001). In multivariate analysis and after adjusting for different baseline characteristics, pts with severe anemia had higher occurrence of a composite of death and adverse cardiovascular events at 1-year compared to those without severe anemia [OR 3.04, 95% CI 1.21 to 5.04; p=0.029]. Conclusion: We objected a low prevalence of ACS patients with severe anemia undergoing PCI (52.2%) but the incidence of ICP in these complex patients has increased in recent years, mainly due to the evolution of PCI over the last 40 years. Severe anemia was strongly associated with increased risk of morbidity and mortality in ACS pts. Funding Acknowledgement: Type of funding source: None